CD169+ Subcapsular Macrophage Role in Antigen Adjuvant Activity - Lisk, Christina; Yuen, Rachel; Kuniholm, Jeff; Antos, Danielle; Reiser, Michael L.; Wetzler, Lee M. (Frontiers in Immunology, 2021)
Vaccines have played a pivotal role in improving public health, however, many infectious diseases lack an effective vaccine. Controlling the spread of infectious diseases requires continuing studies to develop new and improved vaccines. Our laboratory has been investigating the immune enhancing mechanisms of Toll-like receptor (TLR) ligand-based adjuvants, including the TLR2 ligand Neisseria meningitidis outer membrane protein, PorB. Adjuvant use of PorB increases costimulatory factors on antigen presenting cells (APC), increases antigen specific antibody production, and cytokine producing T cells. We have demonstrated that macrophage expression of MyD88 (required for TLR2 signaling) is an absolute requirement for the improved antibody response induced by PorB. Here-in, we specifically investigated the role of subcapsular CD169+ marginal zone macrophages in antibody production induced by the use of TLR-ligand based adjuvants (PorB and CpG) and non-TLR-ligand adjuvants (aluminum salts). CD169 knockout mice and mice treated with low dose clodronate treated animals (which only remove marginal zone macrophages), were used to investigate the role of these macrophages in adjuvant-dependent antibody production. In both sets of mice, total antigen specific immunoglobins (IgGs) were diminished regardless of adjuvant used. However, the greatest reduction was seen with the use of TLR ligands as adjuvants. In addition, the effect of the absence of CD169+ macrophages on adjuvant induced antigen and antigen presenting cell trafficking to the lymph nodes was examined using immunofluorescence by determining the relative extent of antigen loading on dendritic cells (DCs) and antigen deposition on follicular dendritic cells (FDC). Interestingly, only vaccine preparations containing PorB had significant decreases in antigen deposition in lymphoid follicles and germinal centers in CD169 knockout mice or mice treated with low dose clodronate as compared to wildtype controls. Mice immunized with CpG containing preparations demonstrated decreased FDC networks in the mice treated with low dose clodronate. Conversely, alum containing preparations only demonstrated significant decreases in IgG in CD169 knockout mice. These studies stress that importance of subcapsular macrophages and their unique role in adjuvant-mediated antibody production, potentially due to an effect of these adjuvants on antigen trafficking to the lymph node and deposition on follicular dendritic cells.